KAJIAN HUKUM PEMBATALAN SUATU AKTA OTENTIK SEBAGAI LEGAL COVER PARA PIHAK TERKAIT DENGAN SYARAT SAHNYA SUATU PERJANJIAN - Ashinta Sekar Bidari, SH, MH. (RECHTSTAAT, 2014)
This research aimed to find out the condition of authentic deed cancelation and the legal consequence resulting from the authentic deed cancelation. Authentic deed is a legal cover having law certainty value and perfect authentication power for those developing it. This study was a normative law research. The data source addressing the discussion of problem occurring were civil case approach to the authentic deed cancellation and statute approach related to authentic deed. In the approach of civil case number 143/Pdt.G/05/PN.Ska, there was a cancelation on an authentic deed, hibah (bequest) deed. The reason of authentic deed cancelation, in this case hibah deed, was that the accused (hibah recipient) evidently ignored the accuser (hibah giver) when the accuser (hibah giver) befell by calamity, it complied with the provision of Article 1688 clause 3 of Civil Code stating that a hibah (bequest) can be cancelled when the hibah recipient declined to give living benefit to the hibah giver when the hibah giver goes bankrupt. It referred to Article 1320 of Civil Code about the condition of an agreement legality consisting of subjective and objective conditions. A deed can be cancelled when the subjective conditions, agree and competent, were not fulfilled. In this civil case, the subjective condition had been met because the hibah giver had no longer agreed to give hibah to the hibah recipient based on an evidence that the hibah recipient had ignored his/her obligation. The legal consequence of authentic deed (hibah deed) cancelation was that the hibah deed no longer had legal power so that the land and building had been formerly granted and belonged to the accused (hibah recipient) became the Accuser (hibah giver)’s. Keywords: authentic deed, cancellation, legal consequence.